The Relationship Between Red Cell Distribution Width (RDW) Value and Mortality Rate in Neonatorum Sepsis at Murni Teguh Methodist General Hospital Sussana Wesley - Pratama, Muhammad Arief (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
Neonatal sepsis remains the leading cause of morbidity and mortality in neonates. Accurate identification of prognostic factors is essential to improve management and clinical outcomes. This study aims to analyze the relationship between Red Cell Distribution Width (RDW) values and other clinical and laboratory parameters and mortality rates in neonatal sepsis. This cross-sectional study involved 98 neonates with a diagnosis of sepsis at Purely Teguh Methodist Sussana Wesley General Hospital from July to December 2023. Demographic, clinical, and laboratory data are collected and analyzed. The statistical tests used included chi-square, independent t-test, and Mann-Whitney U, with a p<0.05 value considered significant. Of the 98 neonates, 35 (35.71%) died. Septic shock was significantly more common in the group that died (85.71% vs 12.70%, p<0.001). Higher RDW values correlated with increased mortality (17.10% ± 1.72 vs 15.40% ± 1.28, p<0.001). Thrombocytopenia (173.00 ± 152.00 vs 242.50 ± 126.00 x 10³/μl, p=0.048), increased IT ratio (median 0.42 vs 0.28, p=0.018), and higher procalcitonin levels (median 3.25 vs 0.68 ng/ml, p=0.007) were also associated with an increased risk of mortality. Septic shock, increased RDW values, thrombocytopenia, increased IT ratio, and high procalcitonin levels are significant predictors of mortality in neonatal sepsis. The combination of these parameters can improve accuracy in risk stratification and guide more effective clinical management.